PENGGUNAAN MESIN KANTOR TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of technology in the office sector has brought significant changes to employee work methods and administrative procedures. Office machines, as a form of modern technology, play a crucial role in enhancing efficiency and productivity within the office environment. This article comprehensively discusses the impact of office machine usage on employee work productivity, focusing on the benefits gained, changes in work procedures, the role of modern technology and ergonomics, as well as the challenges and drawbacks encountered during implementation. The use of office machines has been proven to accelerate the completion of administrative tasks, improve accuracy and quality of work output, and facilitate communication and coordination among departments. Additionally, the application of ergonomic principles in the use of office machines contributes to increased comfort and health of employees, which indirectly boosts motivation and performance. However, the implementation of office machines also faces various obstacles such as resistance to change, the need for training, acquisition and maintenance costs, and data security risks. Therefore, organizations need to manage the use of office machines optimally by considering technical aspects, human resources, and organizational culture to maximize benefits and minimize risks. This article aims to provide insights for practitioners and academics in understanding and managing office technology to sustainably improve work productivity.